Cortical glutathione levels in young people with bipolar disorder: a pilot study using magnetic resonance spectroscopy. - Godlewska, B; Yip, S; Near, J; Goodwin, G; Cowen, P (2014)
RATIONALE: Glutathione (GSH) is a key scavenger for cellular free radicals, and patients with bipolar disorder may have lowered GSH levels in plasma and in post-mortem brain tissue. OBJECTIVES: The objective of the current study was to use magnetic resonance spectroscopy (MRS) to measure cortical GSH levels in young people with bipolar disorder to determine if lowered GSH might be a useful biomarker of vulnerability to the illness. METHODS: We studied 13 patients with DSM-IV bipolar disorder and 11 healthy age-matched controls using proton MRS in conjunction with the SPECIAL acquisition technique. Voxels were placed in prefrontal and occipital cortex. All patients were clinically euthymic at the time of study and unmedicated. GSH and other relevant neurometabolites were measured relative to creatinine. RESULTS: There was no difference in GSH levels between bipolar participants and controls in either prefrontal or occipital cortex. Similarly, participants showed no difference from controls in other measured cortical metabolites including γ-aminobutyric acid, glutamate and N-acetylaspartate. CONCLUSIONS: This pilot study suggests that levels of cortical GSH are unlikely to be a useful trait biomarker of bipolar disorder in young people with a history of relatively mild mood instability at an early stage of illness. Lowered GSH levels may be relevant to bipolar pathophysiology in more severely ill patients, particular those with significant current mood disturbance.